Environmental radiation on large Japanese field mice in Fukushima reduced colony forming potential in hematopoietic progenitor cells without inducing genomic instability. (3rd June 2022) - Ariyoshi, Kentaro; Miura, Tomisato; Kasai, Kosuke; Goh, Valerie Swee Ting; Fujishima, Yohei; Nakata, Akifumi; Takahashi, Atsushi; Shimizu, Yoshinaka; Shinoda, Hisashi; Yamashiro, Hideaki; Seymour, Colin; Mothersill, Carmel; et al.
Abstract: Purpose: To study the environmental radiation effects of wild animals after the Fukushima Dai-ichi nuclear power plant accident, we assessed effects on hematopoietic progenitor cells (HPCs) in large Japanese field mice ( Apodemus speciosus ). Materials and methods: A. speciosus were collected from three contaminated sites and control area. The air dose-rates at the control and contaminated areas were 0.96 ± 0.05 μGy/d (Hirosaki), 14.4 ± 2.4 μGy/d (Tanashio), 208.8 ± 31.2 μGy/d (Ide), 470.4 ± 93.6 μGy/d (Omaru), respectively. We investigated possible DNA damage and pro-inflammatory markers in the bone marrow (BM) cells. The colony-forming potential of BM cells was estimated by the number of HPC colony-forming cells. Radiation-induced genomic instability (RIGI) in HPCs was also analyzed by quantifying delayed DNA damage in CFU-GM clones. Results: Although no significant differences in DNA damage and inflammation markers in BM cells from control and contaminated areas, the number of HPC colonies exhibited an inverse correlation with air dose-rate. With regard to RIGI, no significant differences in DNA damage of CFU-GM clones between the mice from the control and the three contaminated areas. Conclusions: Our study suggests that low dose-rate radiation of more than 200 Gy/d reduced HPCs, possibly eliminating genomically unstable HPCs.